ISSUES ON IMPROVING FINANCIAL CONTROL AS A FORM OF PUBLIC ACTIVITIES - Ustynova, Iryna P.; Kuzio, Julia V. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: the improvement of state financial control organization should be ensured by the activity of all organizations, which are part of the state monitoring system at all levels of governance. Financial monitoring in Ukraine is a complex institution in the state monitoring system that provides public management and ensures statehood. Present financial state lacks control and central executive bodies and local self-government are responsible for control, ensuring stability and avoidance of budget legislation violations. We outlined the drawbacks in legal regulations of financial monitoring practices. Methods of research: in the work used analytical, described the methodological basis of the research is such methods as general scientific and specially legal methods. The use of a descriptive method made it possible to characterize the overall system of financial control. Using the formal legal method, the forms of application of financial control measures were analyzed. The system method and the analysis method were also applied to determine the practical component of the results of the financial control measures. Results: the issue of financial monitoring is widely discussed in modern doctrine developments in the field of law and public administration. Financial monitoring system is regarded as an institution of financial law. Present-day state growth raises such fundamental question as governance improving which primary function is to monitor and control. The state cannot function properly and develop without well-organized control system over the production, distribution and redistribution of the social product and over other spheres of social life. Control is an integral part of the society growth, and financial control at the present stage is the basic element of ensuring public activity. Discussion: in modern doctrinal developments in the field of law and public administration, the topic of financial control has been developed quite broadly. Financial control is regarded as an institution of financial law. Although there are points of view that this is part of public administration activities, one cannot disagree.